KERJA SAMA PEMERINTAH DAN MASYARAKAT MENGATASI PERMASALAHAN SAMPAH DI KABUPATEN PANGKEP - Alfianita, Alfianita; Setiawati, Budi; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the form of government and community cooperation in overcoming waste problems in Mappasaile Village, Pangkajene District, Pangkep Regency. The research method used is a qualitative research method. Using data collection techniques through observation, interviews, and documentation. Research informants 5 people were determined using a purposive sampling technique. Data validation techniques use source triangulation, technical triangulation, and time triangulation. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. The results of the research show that the form of cooperation between the government and the people of the Mappasaile Village uses Transparency, when carrying out community service; Responsiveness, when the government understands the needs of the community, Consensus on different interests in the community, Equal rights, Effectiveness and efficiency when making regulations related to waste, Accountability by jointly carrying out community service between the government and the community.